Bioethanol from Chlorella sp. as a bioenergy source / Phwan Chai Kee - Phwan , Chai Kee (2019)
High global demand of human energy consumption had caused the overexploitation of fossil fuels resources leading to critical need of environmental issues to develop a sustainable, ecofriendly and cost-effective renewable energy resources. Bioethanol produced from microalgae has been considered “third generation” biofuel to be known as one of the important renewable energy. Microalgae are one of a promising feedstock that rich in carbohydrates content which is a viable criteria for fermentation to ethanol. Pretreatment is an important step to release fermentable sugars before bioethanol fermentation. This study investigates the reducing sugar concentration of microalgal Chlorella species after pretreated with acetic and sulfuric acid in various concentrations (1%, 3%, 5%, 7%,9%), respectively and reducing sugar consumed after fermentation. 3,5-dinitrosalisilat acid (DNS) method, Fourier transform infrared spectroscopy (FTIR), Gas chromatography with flame ionization detection (GC-FID) were used to determine the reducing sugar concentration, functional groups of alcohol bonds after distillation and ethanol concentration. Two-way ANOVA analysis (p<0.05) was carried out to determine the difference between effect of types and concentrations of acid to ethanol content. The ANOVA result indicated there was a significant different of both factors in ethanol content. The highest ethanol yield 0.281 g ethanol/ g microalgal was found in bioethanol sample pretreated with 5% sulfuric acid while 0.23 g ethanol/ g microalgal was obtained by bioethanol sample pretreated with 5% acetic acid.